Design and development of portable RFID for attendance system - Abd Wahab, Mohd Helmy; Abdul Kadir, Herdawatie; Abdul Mutalib, Ariffin; Mohamad Mohsin, Mohamad Farhan (2010)
This paper describes an ongoing project for recording examination attendance using Radio Frequency Identification (RFID).The project is carried out to test in a university, where the system which is named Portable Examination Attendance System (PEAS) is integrated with the existing system for record extraction.The use of RFID technology enables the university management to avoid attendance forms from damages such as tear, lost, and misplaced. This paper describes about the design and development of PEAS in terms of hardware technology and software. In addition, some related works are reviewed and addressed to support this project.As a conclusion, this paper states some future works of this project.